2006
DOI: 10.1590/s1415-47572006000300018
|View full text |Cite
|
Sign up to set email alerts
|

Esterase-D and chromosome patterns in Central Amazon piranha (Serrasalmus rhombeus Linnaeus, 1766) from Lake Catalão

Abstract: This study presents additional genetic data on piranha (Serrasalmus rhombeus Linnaeus, 1766) complex previously diagnosed due to the presence of distinct cytotypes 2n = 58 and 2n = 60. Three esterase-D enzyme loci (Est-D1, Est-D2 and Est-D3) were examined and complemented with chromosomal data from 66 piranha specimens collected from Lake Catalão. For all specimens the Est-D1 and Est-D2 loci were monomorphic. In contrast, the Est-D3 locus was polymorphic with genotypes and alleles being differentially distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…rhombeus) bearing 2n = 58 chromosomes (Nakayama et al, 2001), as well as another karyomorph was identified by chromosomal and molecular analyses (Teixeira et al, 2006), suggesting that S. rhombeus is a complex of species. This hypothesis is strengthened by the present data on 18S rDNA sites, since S. cf.…”
Section: Discussionmentioning
confidence: 97%
“…rhombeus) bearing 2n = 58 chromosomes (Nakayama et al, 2001), as well as another karyomorph was identified by chromosomal and molecular analyses (Teixeira et al, 2006), suggesting that S. rhombeus is a complex of species. This hypothesis is strengthened by the present data on 18S rDNA sites, since S. cf.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, four distinct karyotypes were found in S. maculata (junior synonyme -S. spilopleura Jégu and Santos, 2001) in the confluence of the Negro and Solimões Rivers, Amazon Basin (Nakayama et al, 2000;Centofante et al, 2002), while three karyomorphs were reported in the Paraná Basin population (Cestari and Galetti, 1992b). While S. rhombeus presented a karyotype with 2n = 60; a criptic species presented 2n = 58 and a karyotype probably derived from the 2n = 60 by chromosome fusions (Nakayama et al, 2001), and a third new karyomorph was also reported (Teixeira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In Serrasalmus , for example, three karyomorphs of S . rhombeus Linnaeus 1766 occurring in syntopy were found, which varied both in 2n and in the karyotype formula [ 26 , 27 ]. Different karyomorphs were also observed in specimens of S .…”
Section: Introductionmentioning
confidence: 99%